The role of academics in Turkey's politics: the Mulkiye Junta and the transformation of the Republican People's Party - EMRE, YUNUS (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2014)
Between 1971 and 1973, Bulent Ecevit, an exceptional Third World leader who espoused a social democratic creed, struggled against the military rule by peaceful means. His main supporters in intellectual and ideological terms were a group of professors and politicians known as the Mulkiye Junta. The members of the group were scholars from the Ankara University Faculty of Political Science (previously known as the Mulkiye) and advisors to Ecevit. They supported parliamentary politics, criticized the role of the military in political life and recommended a new direction for the Republican People's Party (RPP). In May 1972, they took over the party administration under the party chairmanship of Bulent Ecevit. After this, the RPP won the highest votes in the 1973 elections. The Mulkiye Junta had central role in the leadership and ideological change in the RPP. This article examines the political thinking of this group and their struggles within the RPP.
Keywords: global periphery; Bulent Ecevit; social democracy; Mulkiye Junta; the Republican People's Party